Stable sampling equilibrium in common pool resource games - Juan Camilo Cárdenas; César Mantilla; Rajiv Sethi (Games, 2015)
This paper reconsiders evidence from experimental common pool resource games from the perspective of a model of payoff sampling. Despite being parameter-free, the model is able to replicate some striking features of the data, including single-peaked frequency distributions, the persistent use of strictly dominated actionsand stable heterogeneity in choices. These properties can also be accurately replicated using logit quantal response equilibrium (QRE), but only by tuning the free parameter separately for separate games. When the QRE parameter is constrained to be the same across games, sampling equilibrium provides a superior fit to the data. We argue that these findings are likely to generalize to other complex games with multiple players and strategies.
Keywords: C73; C91; D03; H41; Q20; 330; common pool resource games; experiments; sampling equilibrium; quantal response equilibrium